Leaflet and digital poster education to improve family knowledge and attitudes toward pediatric fall prevention - Jeni Puspita Sari; Sujiah Sujiah; Rictha Puspita Haryanti (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI), 2026)
Background: Falls are preventable patient-safety events that can cause injury, prolong hospitalization, and increase the burden on children, families, and healthcare services. Family caregivers require clear and accessible education to participate effectively in fall-prevention practices during pediatric hospitalization. Purpose: To compare the effects of education using a leaflet plus a digital poster with education using a leaflet alone on family caregivers' knowledge and attitudes toward pediatric fall prevention. Method: This quasi-experimental study used a pretest-posttest control-group design. Eighty-eight family caregivers of pediatric inpatients were recruited through purposive sampling and allocated to an intervention group (n = 44) or a control group (n = 44). The intervention group received education using a leaflet and a digital poster, whereas the control group received leaflet-based education. Knowledge and attitude scores were assessed before and after the intervention. Within-group changes were analyzed using paired-samples t tests, and between-group differences were examined using an independent-samples t test. Results: Knowledge and attitude scores increased in both groups after education, with larger improvements in the combined-media group. In the intervention group, the mean knowledge score increased from 44.03 to 87.64 and the mean attitude score increased from 55.87 to 87.69. In the control group, the corresponding scores increased from 43.47 to 70.17 and from 53.41 to 73.39. All within-group changes were statistically significant (p < 0.05), and the post-intervention difference between groups was also significant. Conclusion: Education combining a leaflet and a digital poster produced greater improvements in family caregivers' knowledge and attitudes toward pediatric fall prevention than leaflet-based education alone. The combined approach may be incorporated into family-centered patient-safety education in pediatric inpatient settings.